Study on Croton sp. genetic diversity in the Department of Norte de Santander using the internal transcribed spacer (ITS) region of ribosomal DNA (rDNA) (2022)
Genetic variability studies on species with a pharmacological potential are essential for conserving genetic resources. A genetic characterization of a species can guide efforts to collect and conserve germplasm for future breeding programs. The Croton genus belongs to the Euphorbiaceae family, which has approximately 1,300 species, is widely distributed in tropical and subtropical regions of the world, and has a wide range of ethnobotanical and medicinal uses. The aim of this research was to study genetic variability by analyzing sequences of the internal transcribed space region (ITS1 5'-TCCGTAGGGAACCTGCGGC-3' and ITS4 5'-TCCTCCGCTTATGC-3') of ribosomal DNA (rDNA) of a Croton population from forested areas in the Department of Norte de Santander in the municipalities of Chinacota, Pamplona and El Zulia. The results indicated considerable genetic variability in the Croton population, with a nucleotide similarity ranging from 54 to 99% and phylogenetical grouping according to the place of origin. The information gained from the ITS region can be a useful parameter for diversity evaluations and phylogenetic studies since there are no similar studies on Croton in this department in northeastern Colombia.